Transformative Learning, Study Abroad, & Global Service-Learning in Costa Rica/Nicaragua : Program Partner and Host Community Perspectives - Thompson, Kinsey; Pettit, Samantha; Stoeger, Shauna L.; Rice, Tehya M.; Oestreich, Tia (My University, 2012)
The transformative learning theory suggests that students' educational experiences in and outside of the classroom cause disorienting challenges that result in changes in their frames of reference that lead to enriching the meaning of their experiences and, therefore, enhancing their education beyond basic content acquisition. It has been suggested that study abroad excursions with service-learning components offer students transformative learning that develops their critical thinking capacity in terms of their individual selves and the societies around them. To test the hypothesis that study abroad excursions with service-learning components offer transformational learning, this study gauged students' preliminary and posterior opinions on their personal educational and study abroad experiences.
Color poster with text and graphs.
Keywords: Transformative learning; Foreign study; Service learning; Culture and globalization--Costa Rica; Culture and globalization--Nicaragua; College students--Attitudes; Posters